The many faces of peroxisomal disorders: Lessons from a large Arab cohort. Issue 2 (18th December 2018) - Alshenaifi, Jumanah; Ewida, Nour; Anazi, Shams; Shamseldin, Hanan E.; Patel, Nisha; Maddirevula, Sateesh; Al‐Sheddi, Tarfa; Alomar, Rana; Alobeid, Eman; Ibrahim, Niema; Hashem, Mais; Abdulwahab, Firdous; et al.
Abstract : Defects in the peroxisomes biogenesis and/or function result in peroxisomal disorders. In this study, we describe the largest Arab cohort to date (72 families) of clinically, biochemically and molecularly characterized patients with peroxisomal disorders. At the molecular level, we identified 43 disease‐causing variants, half of which are novel. The founder nature of many of the variants allowed us to calculate the minimum disease burden for these disorders in our population ~1:30 000, which is much higher than previous estimates in other populations. Clinically, we found an interesting trend toward genotype/phenotype correlation in terms of long‐term survival. Nearly half (40/75) of our peroxisomal disorders patients had documented survival beyond 1 year of age. Most unusual among the long‐term survivors was a multiplex family in which the affected members presented as adults with non‐specific intellectual disability and epilepsy. Other unusual presentations included the very recently described peroxisomal fatty acyl‐CoA reductase 1 disorder as well as CRD, spastic paraparesis, white matter (CRSPW) syndrome. We conclude that peroxisomal disorders are highly heterogeneous in their clinical presentation. Our data also confirm the demonstration that milder forms of Zellweger spectrum disorders cannot be ruled out by the "gold standard" very long chain fatty acids assay, which highlights the value of a genomics‐first approach in these cases. Abstract :